2012
DOI: 10.1088/0004-637x/753/1/76
|View full text |Cite
|
Sign up to set email alerts
|

The Coronal Abundance Anomalies of M Dwarfs

Abstract: We analyze Chandra X-ray spectra of the M0 V+M0 V binary GJ 338. As quantified by X-ray surface flux, these are the most inactive M dwarfs ever observed with X-ray grating spectroscopy. We focus on measuring coronal abundances, in particular searching for evidence of abundance anomalies related to First Ionization Potential (FIP). In the solar corona and wind, low FIP elements are overabundant, which is the so-called "FIP effect." For other stars, particularly very active ones, an "inverse FIP effect" is often… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 39 publications
(56 reference statements)
6
57
0
Order By: Relevance
“…We initially set elemental abundances to Solar values (Asplund et al 2009), but we found that the spectral fit was improved significantly around 1 keV by allowing the Fe and Mg abundances to drop below Solar values (values of 0.03-0.19 Solar). This is consistent with the "inverse FIP effect" seen in very active stars and M dwarfs (where FIP refers to the first ionisation potential of the element; Wood & Linsky 2010;Wood et al 2012;Laming 2015).…”
Section: X-ray Emissionsupporting
confidence: 85%
“…We initially set elemental abundances to Solar values (Asplund et al 2009), but we found that the spectral fit was improved significantly around 1 keV by allowing the Fe and Mg abundances to drop below Solar values (values of 0.03-0.19 Solar). This is consistent with the "inverse FIP effect" seen in very active stars and M dwarfs (where FIP refers to the first ionisation potential of the element; Wood & Linsky 2010;Wood et al 2012;Laming 2015).…”
Section: X-ray Emissionsupporting
confidence: 85%
“…Objects marked with an X were already included in Wood & Laming (2013). Solid lines bound all of the stars in Wood et al (2012) except for one.…”
Section: Fip Effectmentioning
confidence: 99%
“…The coronae of solar-like stars exhibit a varying degree of the solar-like FIP effect in their X-ray spectra whereas more active cool dwarf stars show an inverse FIP (IFIP) effect. In surveys of M dwarf stars and active binaries, low-FIP elements are under-abundant relative to high-FIP elements e.g., O, Ne, Ar (e.g., Brinkman et al 2001;Telleschi et al 2005;Robrade & Schmitt 2005;Argiroffi et al 2005;Robrade & Schmitt 2006;Wood & Linsky 2006;Liefke et al 2008;Wood et al 2012). Wood & Linsky (2010) firmly established the dependence of the (I)FIP effects on F to K spectral type stars with X-ray luminosity <10 29 ergs s −1 .…”
Section: Introductionmentioning
confidence: 98%